Stock Market’s Reactions to Industrial Accidents: Evidence from Chinese Listed Companies - Wei, J.; Wang, H.; Guo, Xiumei (IGI Publishing, 2014)
This study attempts to explore whether and how stock market responds to industrial accidents. We employ the event study method to look into the responses of stock markets to 83 accidents experienced by various listed companies in China, and explore how industrial accidents influence stock market in the different markets. Findings imply that the stock market shows negative reaction with respect to these accidents. However, as time goes by, the market reaction tapers off. In the bear market, the negative market reaction was highly significant. Small-sized companies, in comparison with other companies, have a most significant reaction to accidents and they also have the worst ability to recover from accidents. The findings of this study can help the investors to better understand how the stock market reacts to the industrial accidents in different market environments and under other conditions.